Dynamic changes in orbitofrontal-hippocampal connectivity linked to cognitive map formation in humans - Yidan Qiu; Huakang Li; Yuanyuan Yang; Shuting Lin; Xiaoyu Zheng; Shuxin Jia; Ruiwang Huang (NeuroImage, 2025)
How the brain coordinates to represent cognitive maps? Although extensive evidence shows the roles of the hippocampus (HIP), parahippocampal cortex (PHC), orbitofrontal cortex (OFC), and retrosplenial cortex (RSC) in spatial navigation, the specific mechanisms by which these brain regions interact to form and use cognitive maps remain unclear. Thus, we employed a task-fMRI during a navigation task in multidimensional abstract spaces to study how navigational complexity, assessed by navigation stages, spatial dimensions, and target distance, affects behavioral performance and brain activation. Our results revealed that the lateral OFC (lOFC) and medial OFC (mOFC) responded differently to navigation stages, and regions of the medial temporal lobe (MTL), including the HIP, PHC, and RSC, were involved in processing target distance. Generalized psychophysiological interaction (gPPI) analysis showed increased connectivity between the lOFC and MTL regions during navigation, and decreased connectivity between the mOFC and MTL regions. These results showed functional divisions within the OFC, with distinct roles for the lateral and medial parts in both activation and connectivity during navigation. Dynamic causal modeling (DCM) further revealed the effective connectivity patterns between these regions, showing that the self-connectivity of the mOFC and HIP contributed to individual differences in behavior. In addition, the self-connectivity of the mOFC and the connectivity from PHC to HIP were predictive of individual navigation strategy preferences. These findings advance our understanding of the neural dynamics underlying abstract spatial cognition, offering new perspectives on how the brain supports adaptive behavior in complex environments.